Association of Mammographic Breast Density with Dairy Product Consumption, Sun Exposure, and Daily Activity. (4th March 2014) - Alipour, Sadaf; Saberi, Azin; Alikhassi, Afsaneh; Bayani, Leila; Hosseini, Ladan
Abstract : Background . Mammographic density is a risk factor, for breast cancer and its association with various factors is under investigation; we carried out a study to assess its relationship with daily dairy intake, sun exposure, and physical activities. Patients and Methods . Women ≥40 years of age were interviewed about habits of dairy product consumption, daily sun exposure and physical activity. Exclusion criteria consisted of history of breast cancer, consumption of calcium and vitamin D supplements, hormone replacement therapy, or renal disease. Mammographic densities were classified according to the classification system of the American College of Radiologists into 4 classes. Results . Overall 703 cases were entered in the study. The mean age was48.2 ± 6.2 years. The most common and least frequent classes of mammographic density were classes 2 and 4, respectively. There was no significant association between mammographic density and rate of dairy consumption, amount of sunlight exposure, and daily physical activity. Conclusion . Relation of sunlight exposure and intake of milk products with mammographic density need further study, while the subject of physical activity can be evaluated by a systematic review and meta-analysis of the existing literature.